Spiroaquilarenes A–E: unprecedented anti-inflammatory sesquiterpene polymers from agarwood of Aquilaria sinensis. Issue 8 (25th February 2022) - Huang, Xiao-Ling; Yan, Yong-Ming; Wang, Dai-Wei; Cheng, Yong-Xian
Abstract : Spiroaquilarenes A–E (1–5 ), a class of sesquiterpene polymers featuring unusual furaneol rings connecting sesquiterpene units, were isolated from agarwood of Aquilaria sinensis and structurally characterized. Abstract : Spiroaquilarenes A–E (1–5 ), a class of sesquiterpene polymers featuring unusual furaneol rings connecting sesquiterpene units, were isolated from agarwood of Aquilaria sinensis . Their structures were identified by spectroscopic analyses and computational methods. Compounds 2 and 3 were found to dose-dependently inhibit the production of TNF-α, IL-6, and nitrite oxide and the activation of NF-κB in LPS-induced RAW264.7 cells.